Early ovine preantral follicles have a potential to grow until antral stage in two‐step culture system in the presence of aqueous extract of Justicia insularis. Issue 8 (17th June 2019) - Mbemya, Gildas Tetaping; de Sá, Naiza Arcângela Ribeiro; Guerreiro, Denise Damasceno; de Sousa, Francisca Geovania Canafístula; Nguedia, Sylvain Njina; Alves, Benner Geraldo; Santos, Francielli Weber; Pessoa, Otília Deusdênia Loiola; Comizzoli, Pierre; Figueiredo, José Ricardo; Rodrigues, Ana Paula Ribeiro
Abstract: The objective of this study was to determine whether preantral follicles cultured in vitro for 7 days within ovine ovarian cortical strips could be isolated at the secondary follicles (SF) and grown until antral stage during an additional 6 days period of in vitro culture in the presence of aqueous extract of Justicia insularis . Fresh ovarian fragments from 16 adult sheep were fixed for histological analysis (Control 1) or in vitro cultured individually in α‐MEM + supplemented with 0.3 mg/ml J. insularis (Step 1) for 7 days. Part of the fragments then were fixed for histological analysis (in vitro culture group). Remaining fragments were exposed stepwise to increasing trehalose concentrations before immediate isolation of SF and viability assessment (Control 2) or after 6 days of culture in α‐MEM ++ supplemented with 0.3 mg/ml J. insularis (Step 2). In Step 1, percentage of follicular activation was 80%. In Step 2, a significant increase ( p < 0.05) in follicular diameter and antrum formation within 6 days in vitro culture of isolated follicles was achieved. The total antioxidant capacity from both steps significantly increase ( p < 0.05) from day 2 to day 6. Confocal analysis of oocytes showed 57.14% oocytes with homogeneous distribution and 42.86% with peri‐cortical distribution. In conclusion, SF can be successfully isolated from sheep ovarian cortex after 7 days of culture and are capable of surviving and forming an antral cavity if cultured in vitro for an additional 6 days in the presence of 0.3 mg/ml J. insularis .